2019
DOI: 10.1063/1.5110046
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz field confinement and enhancement in various sub-wavelength structures

Abstract: Terahertz plasmonics is one of the fascinating research fields that includes diverse applications in nonlinear terahertz optics and nano-optics, as well as studies about strong localization and enhancement of millimeter waves. Recent advanced lithography techniques enable one to reach the confinement scale of electromagnetic waves down to subnanometer, which corresponds to wavelength/10 000 000. In particular, the strong electric-field enhancement in metal gaps can produce atomically strong field exceeding ∼10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 134 publications
0
5
0
Order By: Relevance
“…The coupling efficiency can be improved by using not a point source, but a diffraction grating with a period much less than the wavelength and with the reciprocal grating vector is equal to the EPP wavelength. There are now many other routes of efficient coupling of the bulk field to the deeply subwavelength plasmonic terahertz modes [36]. This suggests that the chiral currents may be regarded as an extremely efficient source of SHG in the terahertz range.…”
Section: Resultsmentioning
confidence: 99%
“…The coupling efficiency can be improved by using not a point source, but a diffraction grating with a period much less than the wavelength and with the reciprocal grating vector is equal to the EPP wavelength. There are now many other routes of efficient coupling of the bulk field to the deeply subwavelength plasmonic terahertz modes [36]. This suggests that the chiral currents may be regarded as an extremely efficient source of SHG in the terahertz range.…”
Section: Resultsmentioning
confidence: 99%
“…The latter approach has shown that THz electric fields can be enhanced by more than an order of magnitude. 31,32 This could be used to realize fields exceeding tens of kV/cm that compares favorably with the recent work using FEL to study harmonic generation in graphene, which required a field of $10 kV/cm for observation of the third harmonic. 1 This resonator approach could also be combined with THz pulse generation through QCL mode locking for further enhancements of the peak power densities and ultrafast exitations.…”
mentioning
confidence: 80%
“…[26][27][28][29][30] Metallic resonator-based planar metasurface cavity confinement could be easily accessed for inducing light-matter interactions. [19,[31][32][33] Specifically, the large in-plane confinement of the electromagnetic energy in these structures has attracted enormous interest in switching and modulation applications. [34][35][36] Moreover, such metasurfaces are extremely sensitive to external perturbations created by the passive and active material environment.…”
Section: Active Energy-efficient Terahertz Metasurfaces Based On Enha...mentioning
confidence: 99%